Reduction of Total Suspended Solids, Turbidity and Colour of Palm Oil Mill Effluent using Hybrid Coagulation-Fltrafiltration Process - Ng, W. Q.; Lai, S. O.; Chong, K. C.; Lee, S. S.; Koo, C. H.; Chong, W. C. (Journal of Applied Membrane Science & Technology, 2018)
High consumption and production of palm oil have led to the massive generation of palm oil mill effluent (POME). This study was intended to reduce the total suspended solids (TSS), turbidity and colour using hybrid coagulation-ultrafiltration process. POME was pre-treated with coagulation process using polyaluminium chloride (PAC) and optimization of operating condition for coagulation process was performed. The coagulation results revealed that optimum pH, dosage of coagulant and rapid mixing speed were pH 4, 600 mg/L and 200 rpm, respectively. It achieved the highest percent reduction of TSS, turbidity and colour with 99.74%, 94.44% and 94.60%, respectively. Ultrafiltration (UF) membrane was fabricated using polyethersulfone (PES), polyvinylpyrrolidone (PVP) and titanium dioxide (TiO2Â) nanoparticle. Different concentrations ranging from zero and 1.0 wt% of TiO2 nanoparticles were added into the dope solution. The characterization studies of UF membranes confirmed that higher concentration of TiO2 provided higher pure water permeability and more porous structure in the UF membranes. The amount of TiO2 in membrane only affected the permeate flux but had no obvious effects on the reduction of TSS, turbidity and colour. The optimum transmembrane pressure was found to be 3 bar, resulting in the greatest reduction of TSS, turbidity and colour.